INVESTIGATIONS FOR ENHANCING THE APPLICATION DOMAIN OF FUSED DEPOSITION MODELLING PROCESS (Journal of Mechanical Engineering, 2017)
In the recent past, various studies have been reported on the development of in-house fused deposition modelling (FDM) filament, in order to increase the application domain of the process. But hitherto very less have reported on the effect of reinforcement type (such as: SiC, Al2O3 and Fe powder etc.) on the melt flow index (MFI) of the polymer matrix composite (PMC) to be used as FDM filament. In the present research work, an effort has beenmade to investigate the effect of selected proportions of filler, matrix (nylon-6) and extrusion load on the MFI of reinforced FDM filament. Experimental study was conducted on melt flow indexer (MFIer) as per ASTM-D1238-95 standard and signal to noise ratio was calculated to find out the effect of input process parameters on MFI of hybrid filament. It has been found that proportion of filler in matrix, type of filler material and extrusion load contributed about 16.62%, 1.23% and 76.72% respectively.